HPIP is upregulated in liver cancer and promotes hepatoma cell proliferation via activation of G2/M transition. Issue 10 (3rd September 2013) - Xu, Xiaojie; Jiang, Chengying; Wang, Shibin; Tai, Yanhong; Wang, Tao; Kang, Lei; Fan, Zhongyi; Li, Shuyue; Li, Ling; Fu, Jing; Liu, Jiahong; Ji, Quanbo; et al.
Abstract Hematopoietic pre‐B‐cell leukemia transcription factor (PBX)‐interacting protein (HPIP) has been shown to play a role in cancer development and progression. However, the detailed role of HPIP in cancer cell growth and the exact mechanism by which HPIP regulates cancer cell proliferation remains unclear. Here, we report that HPIP is overexpressed in most of 328 liver cancer patients and regulates hepatoma cell proliferation through G2/M checkpoint activation. HPIP increased anchorage‐dependent and ‐independent growth of human liver cancer cell lines. The amino acid region 531–631 of HPIP was important for its modulation of liver cancer cell growth. The increased effects of HPIP on liver cancer cell proliferation were associated with activation of the G2/M cell‐cycle concomitant with a marked increase of cyclin B1 and the inhibition of the negative G2/M phase regulator GADD45α. HPIP knockdown dramatically suppressed the growth of HepG2 liver cancer cells in nude mice. These data highlight the important role of HPIP in liver cancer cell growth and suggest that HPIP may be a good target for liver cancer therapy. © 2013 IUBMB Life, 65(10):873‐882, 2013